Perception and Practice of Shisha Smoking among Undergraduate Students of Faculty of Allied Health Sciences, Bayero University Kano - Rajah, Amina Suleiman; Sulaiman, Abdullahi; Dalhatu, Adamu; Haddad, Mahfuz Mohammed; Murtala, Hassan Hassan; Nuhu, Khadija Nasidi; Dandago, Sumayya Kabir (Journal of Practical Nurse Education and Practice, 2025)
Tobacco smoking remains a significant public health challenge, with shisha (waterpipe) smoking gaining popularity among university students who perceive it as a safer alternative to traditional cigarette smoking. This study aimed to explore the perception and practice of shisha smoking among undergraduate students at the Faculty of Allied Health Sciences, Bayero University, Kano. A cross-sectional survey was conducted involving 261 students, utilizing a structured self-administered questionnaire to assess their awareness, attitudes, and behaviours related to shisha smoking. The results indicated that 96.9% of respondents were aware of shisha, yet only 13% reported having smoked it. Although many participants recognized the harmful effects of shisha, misconceptions persisted regarding its safety compared to cigarettes, with 43.3% believing that the water in shisha filters harmful toxins. The findings further revealed that 62.8% of respondents acknowledged shisha contains harmful toxins. Awareness of nicotine presence was notable, with 58.5% recognizing it as an ingredient. Health risks were the strongest deterrent, as 51.3% strongly agreed that shisha causes health problems. Among influencing factors, the aromatic flavor of shisha was the most cited, with 37.5% agreeing it encourages smoking. Religious concerns were a key deterrent, with 42.9% strongly agreeing it discourages use. Chi-square analysis showed that age (χ² = 4.12, p = 0.042), ethnicity (χ² = 6.23, p = 0.043), and area of settlement (χ² = 8.88, p = 0.012) were significantly associated with shisha smoking, while other socio-demographic factors were not. Awareness of shisha had no significant association with its practice (χ² = 1.18). The study highlighted high awareness of but persistent misconceptions about shisha’s safety, with social acceptance and flavours driving its use, whereas health concerns and stigma served as strong deterrents, emphasizing the need for more sensitization and health education to promote informed choices and reduce smoking prevalence.